Implementation methodologies of BIM in construction projects of Kazakhstan - Yertay, Yerassyl (Nazarbayev University School of Engineering and Digital Sciences, 2019)
The subject of this proposal developed from a personal interest in BIM-based methods on construction projects of Kazakhstan. In the age of advancement, Building Information Modelling is gaining popularity around the globe because of its potential. BIM is a very intricate tool in the planning and execution stage. As BIM consists of all domain of construction, it is equally important to understand its effect on planning, especially on scheduling, visualization, and cost. In their paper “Acceptance of construction scheduling visualizations: bar-charts, flowline-charts, or perhaps BIM?”, Rolfsen and Merschbrock point out that even the most successful country from BIM, Norway, does not totally use BIM-based scheduling on their construction projects. However, the rapid development of BIM on construction projects compels not to lose the relevance of the technology in the civil engineering sector. This research focuses on several benefits of BIM technology and provides a technical task for the designing of the BIM model in construction projects of Kazakhstan.